Analysis of tree rows and their impact on the structural and service engineering elements of Iskenderun Street in the Tartous city - عيسى أحمد; أسامة رضوان; طلال أمين (Latakia University Journal -Biological Sciences Series, 2023)
This study was conducted in Iskenderun Street, which extends from Iskenderun roundabout to Bank Audi roundabout, according to the east-west direction in the city of Tartous in 2022. The research aimed to analyze the tree rows of this street and study the relationship of its trees with the structural and service engineering components of it, where the ideal condition of the tree species planted in this street was estimated. The results of the research showed the presence of plant diversity in Iskenderun Street, which recorded (13) plant species distributed over (12) families, the most important of which are the brilliant fig, azedracht, sapphire, oriental tannins, and aromatic cypress, which added beauty to the street and a botanical richness of these Rows, and the results of the research showed the presence of prominent cuts in the tree rows of the street. Concerning the evaluation of tree species, the fan palm scored a good perfect score of 7.53 points, while the assessment of the bright fig was below the perfect score of 6.93 points.With regard to the relationship of trees to some engineering elements of the street, the results showed that the standard dimensions between planted trees and service elements were not taken into account.